Determinants of Firm Performance Based on Investment Opportunities and Capital Structure - Saifi, Muhammad; Putri, Intan Lifinda Ayuning; Setyono, Langgeng (LifeSciFi, 2025)
This research investigates the impact of the Investment Opportunity Set (IOS) and capital structure on the performance of manufacturing firms in Indonesia. It explores how these two factors influence the enhancement of firm performance. A quantitative method was applied, utilizing secondary data sourced from the financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, selected through purposive sampling. The data were analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach. The findings reveal that both IOS and capital structure significantly affect firm performance. The study enriches the discourse on agency and signaling theories while offering managerial insights for optimizing capital structure and formulating strategic investment decisions to improve business competitiveness and operational efficiency. Additionally, it emphasizes the necessity of aligning financial policies with potential growth to foster sustainable value for stakeholders. Furthermore, it highlights the importance of aligning financial strategies with growth opportunities to ensure long-term value creation for stakeholders.